2002
DOI: 10.1074/jbc.m111922200
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Potential-controlled Inhibition of Cytochromec Oxidase by Zinc

Abstract: Like many voltage-sensitive ion pumps, cytochrome c oxidase is inhibited by zinc. Binding of zinc to the outside surface of Rhodobacter sphaeroides cytochrome c oxidase inhibits the enzyme with a K I of < 5 M when the enzyme is reconstituted into phospholipid vesicles in the presence of a membrane potential. In the absence of a membrane potential and a pH gradient, millimolar concentrations of zinc are required to inhibit. This differential inhibition causes a dramatic increase in the respiratory control ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
115
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(132 citation statements)
references
References 51 publications
17
115
0
Order By: Relevance
“…The specific activity in the absence of M 2ϩ , ϳ8 mol e Ϫ min Ϫ1 mg Ϫ1 , is equal to that of complex I in the inner mitochondrial membrane (30 in Group 12, is also effective. A similar trend was reported previously for modulation of the catalytic activity of cytochrome c oxidase by divalent cations (33). The concentration dependence of the Zn 2ϩ inhibition is described below.…”
Section: The Effect Of Divalent Cations On the Nadh:decylubiquinonesupporting
confidence: 79%
See 2 more Smart Citations
“…The specific activity in the absence of M 2ϩ , ϳ8 mol e Ϫ min Ϫ1 mg Ϫ1 , is equal to that of complex I in the inner mitochondrial membrane (30 in Group 12, is also effective. A similar trend was reported previously for modulation of the catalytic activity of cytochrome c oxidase by divalent cations (33). The concentration dependence of the Zn 2ϩ inhibition is described below.…”
Section: The Effect Of Divalent Cations On the Nadh:decylubiquinonesupporting
confidence: 79%
“…Similar modes of zinc inhibition have been observed in many other protontranslocating membrane proteins. Zn 2ϩ inhibits the bacterial photosynthetic reaction center by binding to amino acid residues that mediate proton transfer to Q B (51,52); it probably inhibits the cytochrome bc 1 complex by preventing proton egress from the Q O site (17,31), and it inhibits proton transfer in cytochrome c oxidase by binding at the entrance to one or more proton channels (18,32,33,35). In the future, zinc binding may be applied to localize proton channels or other key structural catalytic features in complex I in a similar fashion.…”
Section: Is Complex I Inhibition Relevant To Zn 2ϩmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from earlier studies have shown that the activity of wild-type CytcO is inhibited by zinc ions (Zn 2+ ) (28)(29)(30)(31)(32)(33)(34)(35). One of the suggested Zn 2+ binding sites is located near Asp-132, consistent with structural data of the mitochondrial CytcO (36).…”
Section: Resultssupporting
confidence: 63%
“…Because proton uptake through the D pathway presumably is not rate limiting for this activity, any effects of Zn 2+ addition may reflect binding to other sites (32)(33)(34). We observed the same decrease in activity upon addition of Zn 2+ to the N139T/D132N as to the wildtype CytcO, which indicates that zinc binding to the other sites was not affected by the D pathway mutations.…”
Section: Resultssupporting
confidence: 52%